Assessment of the water fluxes from the Black Sea to the Mediterranean using a coastal HF radar - Κοκκίνη, Ζωή (2019)
A two-site WERA High Frequency radar (HF radar) system, named “Dardanos”, was installed in November 2009 on the eastern coast of Lemnos Island, North Aegean Sea,with an initial purpose to monitor the surface inflow of Black Sea waters exiting from the Dardanelles Strait, as well as to constitute a coastal management tool for incidents of oil- pollution or search-and-rescue operations. This thesis aims to exploit this recently installed coastal High-Frequency radar system in an effort to quantifying the water inflow from the Dardanelles into the North Aegean Sea. The installation and the almost two years of continuous operation of the “Dardanos” system has enabled, for the first time, the estimation of the volume of the waters entering in the Aegean through the Dardanelles, at half-hourly intervals. Various efforts of estimating lateral fluxes are presented. An innovation required in order to estimate surface lateral fluxes from HF-radar measurements by estimating the mixed-layer depth (MLD), combining HF-radar surface current velocities derived by the “Dardanos” system, and wind-speed measurements. The results of this study are compared with estimates from literature and existing exchange models for confirmation. These results can be used as a new tool that will provide improved knowledge of the Mediterranean exchanges with the Black Sea in almost near real time. Furthermore, the new method we have developed for estimating mixed-layer depth and lateral volume fluxes by HF radar and wind-stress data can be applied at several other HF radar installations globally, especially locations at Straits (like the Straits of Gibraltar and Messina), where the laterally advected surface layer plays a crucial role in the climatological functioning of the semi-enclosed seas connected by the respective Strait.